Family configurations and arrangements in the transnational mobility of early-career academics: Does gender make twice the difference? - Toader, Alina; Dahinden, Janine (Migration Letters, 2018)
Previous studies have pointed out the highly gendered character of academia in general and international mobility in particular: women academics are confronted with a ‘glass ceiling’, and they are less geographically mobile than men, mainly as a result of family obligations. This paper examines whether gender plays twice a role in how women and men consider family arrangements in regard to a long-term post-PhD period of transnational mobility. Using data from an online survey and face-to-face interviews at the Universities of Cambridge and Zurich, we focus first on family configurations when academics decide to become mobile, then on how the family arrangements evolve while abroad. We show that the transnational mobility of academics has become more complex and varied than the ‘classical model’ of mobile academic men and non-mobile or ‘tied mover’ women. While having a child continues to impact gender roles, institutional characteristics in the context of mobility also play a role that needs to be further analysed.